Governança Territorial um primeiro passo na construção de uma proposta teórico-metodológica - Valdir Dallabrida Roque (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2003)
Governance can be understood as the use of power and authority to conduct a country or a region, realizing themechanism, actions and institutions in wich citizens and groups articulate their interests since minimal consensus.Territorial governance happens through the action of different actors/agents in the institutions and organizationsof civil society in social and territorial nets. The definition of new ways for the territorial or regional developmentdepends on the constitution and emergency of a new social and territorial bloc that, in a social correctionprocess, tries to build consensus, by the action of different actors/agents, the integration of their differentpurposes and world view, resulting on the social and territorial pact; in other words: the political project for theregions development. But the region needs to amass political power, realizing the dimension of the discentralizationand social correction, power that is able to produce consensus, to produce the collective, the groups interests.As result, the region may build the possibility of becoming subject to its own development.